The Influence of Audio Visual Media on Improving Learning Outcomes of Adab Material For Parents And Teachers In Class VIII-A Mts Al Karim Gondang Nganjuk Academic Year 2023/2024 - Nuraini, Siti; Badi'ah; Anis Humaidi; Toyyibah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The learning outcome is the desired behavioral change or learning goals achieved by students after participating in an educational program. The Akidah Akhlak (Faith and Morality) learning outcomes at MTs Al Karim Gondang Nganjuk, especially in class VIII-A, are currently categorized as average, but there is potential for further improvement into the excellent category. This research aims to determine the influence of audiovisual media on improving the learning outcomes of adab (manners) material for parents and teachers in class VIII-A at MTs Al Karim Gondang Nganjuk. The research adopts a quantitative approach, incorporating numerical data collection and interpretation processes. It is classified as Classroom Action Research (CAR), conducted by teachers in their own classrooms through planning, implementation, and reflective collaborative and participative actions. The goal is to enhance the teacher's performance, leading to improved student learning outcomes. The findings of this research indicate that the use of audiovisual media has a significant impact on enhancing the learning outcomes of adab material for parents and teachers in class VIII-A at MTs Al Karim Gondang Nganjuk. The scores range from a minimum of 85 to a maximum of 100, achieving a 100% completion rate.